2021
DOI: 10.7160/eriesj.2021.140406
|View full text |Cite
|
Sign up to set email alerts
|

A Joint Assessment of Reasoning about General Statements in Mathematics and Biology

Abstract: This contribution belongs to a larger empirical study that focuses on issues related to the implementation of inquiry-based learning and formative assessment in science and mathematics education, while it also refers to the issue of STEM education. Here, we discuss the two topics from the perspective of professional preparation of primary school teachers. We employ an educational tool called Concept Cartoons and perceive it as a common diagnostic tool for investigating modes of reasoning about general statemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
0
0
Order By: Relevance
“…Generally, a pupil with a high IQ is expected to have good results at school (see, e.g., Jalili et al, 2018), and a learner with higher levels of SR could be expected to be a superior problem solver (Tajudin and Chinnappan, 2015). Research also has shown (e.g., Hand et al, 2001;Samková et al, 2021) that reasoning skills represent a set of broadly transferable skills across science and mathematics, and teaching scientific reasoning has a lasting Electronic ISSN 1803-1617 impact on general learning ability not only in science but also in mathematics. Hilbert et al (2019) exposed in their research with Austrian students that the grade in mathematics was best predicted by reasoning at the age of 11-12.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, a pupil with a high IQ is expected to have good results at school (see, e.g., Jalili et al, 2018), and a learner with higher levels of SR could be expected to be a superior problem solver (Tajudin and Chinnappan, 2015). Research also has shown (e.g., Hand et al, 2001;Samková et al, 2021) that reasoning skills represent a set of broadly transferable skills across science and mathematics, and teaching scientific reasoning has a lasting Electronic ISSN 1803-1617 impact on general learning ability not only in science but also in mathematics. Hilbert et al (2019) exposed in their research with Austrian students that the grade in mathematics was best predicted by reasoning at the age of 11-12.…”
Section: Discussionmentioning
confidence: 99%